2015
DOI: 10.14444/2053
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Round vs. Rectangular Expandable Cage Endcaps to Spinal Stability in a Cadaveric Corpectomy Model

Abstract: BackgroundExpandable cages are gaining popularity in anterior reconstruction of the thoracolumbar spine following corpectomy as they can provide adjustable distraction and deformity correction. Rectangular, rather than circular, endcaps provide increased resistance to subsidence by spanning the apophyseal ring; however their impact on construct stability is not known. The objective of this study was to investigate the contribution of expandable corpectomy cage endcap shape (round vs. rectangular) and fixation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…During the testing the stiffness for both lateral bending and torsion decreased significantly in most of the specimens compared with the intact state (phase I). These findings correspond both to those of Wong et al, 32 who found kyphoplasty as a stand-alone treatment was unable to restore the stiffness of an intact specimen in vertebral burst fractures and to those of Mundis et al, 33 who described an increased motion in lateral bending for expandable cages . Furthermore, the approach in this study appears to show similar results compared to a cement augmentation, which did also not show an improvement in torsional stiffness ( P = .72).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…During the testing the stiffness for both lateral bending and torsion decreased significantly in most of the specimens compared with the intact state (phase I). These findings correspond both to those of Wong et al, 32 who found kyphoplasty as a stand-alone treatment was unable to restore the stiffness of an intact specimen in vertebral burst fractures and to those of Mundis et al, 33 who described an increased motion in lateral bending for expandable cages . Furthermore, the approach in this study appears to show similar results compared to a cement augmentation, which did also not show an improvement in torsional stiffness ( P = .72).…”
Section: Discussionsupporting
confidence: 89%
“…However, lag-screws as a stand-alone solution do not seem to improve the specimen’s stiffness significantly. This corresponds to other studies that have dealt with lag-screws, 37 as well as studies dealing with kyphoplasty 32 or cages 33 as stand-alone treatments in vertebral fractures. Furthermore, a decreasing IVS appeared during the testing, which correlates to a progressive collapse of the IVD into the vertebral body and might be the reason for repeatedly reported vertebral nonunion.…”
Section: Discussionsupporting
confidence: 78%
“…However, the stability of conventional pedicle screw fixation for patients with osteoporosis is significantly reduced due to lumbar osteoporosis, and it is difficult to achieve a solid internal fixation effect ( 8 ). Expansive pedicle screw can fix the vertical axial section through the front expansive effect ( 9 ), thus forming the triangular support ( 10 ), and significantly increasing the screw bonding ( 11 ); at the same time, the surrounding bone trabecula is appropriately compressed, thereby further improving the bone density and the stability of internal fixation ( 12 ). In addition, the front end of internal fixation screw after expansion can expand to both sides, thus effectively embedding into the bone and better improving the anti-rotation capacity of the screw ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…We prefer to use a wide-footprint cage packed with locally collected morselized autograft and the surgeon's choice of allograft. Wide footprint rectangular cages (such as X-CORE ® , NuVasive, Inc.) span the hard cortical bone edges of the adjacent vertebral bodies and may help to decrease subsidence (41)(42)(43). This presents as one of the greatest advantages of the lateral approach compared to a posterolateral approach, where only a circular footplate cage can be placed.…”
Section: Surgical Approach and Considerationsmentioning
confidence: 99%